2012
DOI: 10.1016/j.jmb.2012.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Requirements for Combinatorial Recognition of Histone H3 by the MRG15 and Pf1 Subunits of the Rpd3S/Sin3S Corepressor Complex

Abstract: The transcriptional output at a genomic locus in eukaryotes is determined, in part, by the pattern of histone modifications that are read and interpreted by key effector proteins. The histone deacetylase activity of the evolutionarily-conserved Rpd3S/Sin3S complex is crucial for suppressing aberrant transcription from cryptic start sites within intragenic regions of actively transcribed genes. Precise targeting of the complex relies on the chromatin binding activities of the MRG15 and Pf1 subunits. Whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 45 publications
5
26
0
Order By: Relevance
“…1F, we consistently found that both PHD1 and PHD2 preferentially bound to the N-terminal region (residues 1-20) of the H3 tail. This result is consistent with previous analyses of PHD1 (22,23). Interestingly, we also found that trimethlyation of K4 (H3K4me3) decreases the ability of both PHD1 and PHD2 to bind N-terminal H3 1-20 peptides, suggesting that these domains bind to the extreme N terminus of H3 and are affected by N-terminal post-translational modifications.…”
Section: Rco1 Contains Two Phd Fingers That Bind To the N Terminus Ofsupporting
confidence: 93%
See 1 more Smart Citation
“…1F, we consistently found that both PHD1 and PHD2 preferentially bound to the N-terminal region (residues 1-20) of the H3 tail. This result is consistent with previous analyses of PHD1 (22,23). Interestingly, we also found that trimethlyation of K4 (H3K4me3) decreases the ability of both PHD1 and PHD2 to bind N-terminal H3 1-20 peptides, suggesting that these domains bind to the extreme N terminus of H3 and are affected by N-terminal post-translational modifications.…”
Section: Rco1 Contains Two Phd Fingers That Bind To the N Terminus Ofsupporting
confidence: 93%
“…Finally, we note that although a previous survey of yeast PHD domains was performed using solution peptide pulldowns (22), our studies differ in regards to the ability of PHD1 and PHD2 to bind H3K36me3, a result that is also true for the characterized PHD1 domain of the human Rco1 counterpart, Pf1 (23). We note that PHD1 and PHD2 expression and maintaining their stability in vitro was found to be extremely difficult, and further, that binding and washing conditions greatly impacted weak interactions and nonspecific binding.…”
Section: Discussionmentioning
confidence: 74%
“…S1 D and E) (19,20). This prompted us to investigate whether H3K36me3 was required for MRG15-mediated PALB2 chromatin association.…”
Section: Resultsmentioning
confidence: 99%
“…To identify the molecular basis underlying the impact of Pf1 on nucleolar structure and function, we aimed to identify novel Pf1-interacting proteins. To do so, we generated Flag-tagged constructs of wild-type Pf1 and two Pf1 variants with point mutations unable to interact either with MRG15 or with histone H3 (the Pf1 F210A and Pf1 D57N mutants, respectively [5,31]). We then stably expressed the three constructs in HeLa S3 cells, extracted nuclear proteins, immunoprecipitated protein complexes containing the Pf1 construct using anti-Flag beads, and analyzed the protein composition of the precipitated complexes by liquid chromatography-tandem mass spectrometry (LC-MS/MS).…”
Section: Resultsmentioning
confidence: 99%